Significance of Food Security and Safety behind India’s Sustainable Urban Development - Jhinuk Gupta (International Journal of Nutritions, 2024)
The foundation of sustainable urban development lies on the steps taken by a city to reduce its climate change." Multiple aspects of it primarily include water supply, health care, affordable housing, transportation, electricity and sanitation. The most important goal of any sustainable city or smart city is to secure “healthy and safe life” for its people without losing the existing natural resources. Foundation of “healthy life” originates from sufficient availability and right intake of food by people from all economic classes. But unfortunately this fundamental factor of nutrition and food security is often not given importance during designing sustainable smart cities. It is also not realized that food security cannot be achieved without ensuring food safety, as consumption of unsafe food does not lead to a sustainable society. Warranting food safety and security is a big challenge for any country. The problem amplifies even larger in case of developing countries including India. A food may be unsafe for consumption due to both chemical and microbiological reasons, incidentally or intentionally. Therefore, it will be highly beneficial to know about different aspects of food security and safety hazards before planning for building a smart city. This article targets to identify the vital challenges encountered by Indian towns and cities with respect to food safety and security and suggest possible avenues to overcome those. It also includes the initiatives taken by India to build smart cities.
Keywords: Food safety, Food Adulteration; Food security; Smart cities; Sustainable urban development